2022
DOI: 10.1038/s41598-022-24945-5
|View full text |Cite
|
Sign up to set email alerts
|

Creating a kidney organoid-vasculature interaction model using a novel organ-on-chip system

Abstract: Kidney organoids derived from human induced pluripotent stem cells (iPSCs) have proven to be a valuable tool to study kidney development and disease. However, the lack of vascularization of these organoids often leads to insufficient oxygen and nutrient supply. Vascularization has previously been achieved by implantation into animal models, however, the vasculature arises largely from animal host tissue. Our aim is to transition from an in vivo implantation model towards an in vitro model that fulfils the adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…They have also revealed the combination of vascular endothelial growth factor (VEGF) with other biomechanical stimuli can synergistically improve the vascularization of kidney organoids. Furthermore, Menéndez et al reported that co-culture of human umbilical vein endothelial cells (HUVECs) with kidney organoids in a perfusable microfluidic organ on chip leads to endothelial cell migration and vascularization in the kidney organoids [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…They have also revealed the combination of vascular endothelial growth factor (VEGF) with other biomechanical stimuli can synergistically improve the vascularization of kidney organoids. Furthermore, Menéndez et al reported that co-culture of human umbilical vein endothelial cells (HUVECs) with kidney organoids in a perfusable microfluidic organ on chip leads to endothelial cell migration and vascularization in the kidney organoids [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another approach has been the addition of endothelial-promoting cytokines such as VEGF-A to the organoid differentiation medium, but while this expands angioblast cell numbers, it fails to support the formation of an integrated vascular network 20 . Strategies outside of media supplementation include the use of fluidic culture systems that promote vascular growth and survival [19][20][21] , and transplantation into immunodeficient mice, where the host vessels invade the xenograft 24,25 . However, these are cumbersome, low throughput and technically complicated to set-up for routine organoid experiments.…”
Section: Discussionmentioning
confidence: 99%
“…; https://doi.org/10.1101/2023.05. 30.542848 doi: bioRxiv preprint methods similar to other organ systems including flow enhancement with chips [19][20][21] , decellularizing/recellularizing ECM 22 , bioprinting 23 , renal subcapsular transplantation 24,25 , and VEGF supplementation 26 . However, these methods still leave multiple unmet needs 27 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the still ongoing use of animals for the maturation of tissues presents further problems in standardization and production quality, calling for new ways to recreate functional vascularized and perfused tissues in vitro. Therefore, culture systems, including organs-on-a-chip, [26,[94][95][96] capable of growing a vascular network with controlled fluid flow are necessary to transport nutrients to the organoids and facilitate waste removal to stimulate differentiation. The creation of a mature human vascular network in organoids is crucial in the context of modeling diseases that affect the vascular system and for studying the interplay between endothelial-epithelial compartments.…”
Section: Materials That Support and Direct The Formation Of Organoidsmentioning
confidence: 99%